2012
DOI: 10.1155/2012/167132
|View full text |Cite
|
Sign up to set email alerts
|

Macroprolactinemia: Diagnostic, Clinical, and Pathogenic Significance

Abstract: Macroprolactinemia is characterized by a large molecular mass of PRL (macroprolactin) as the main molecular form of PRL in sera, the frequent elevation of serum PRL (hyperprolactinemia), and the lack of symptoms. Macroprolactin is largely a complex of PRL with immunoglobulin G (IgG), especially anti-PRL autoantibodies. The prevalence of macroprolactinemia is 10–25% in patients with hyperprolactinemia and 3.7% in general population. There is no gender difference and a long-term followup demonstrates that macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
112
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 44 publications
2
112
0
4
Order By: Relevance
“…It has been generally accepted that a PEG-precipitation ratio greater than 60% (recovery less than 40%) is the cut-off value for the diagnosis of macroprolactinemia. This is because there is no a clear-cut value of "substantial increase", but conventionally a diagnosis of macroprolactinemia is made when more than 30-60% of PRL is in 11 the macroprolactin form of GFC [6,9,24,[26][27][28]. Precipitation with PEG is a widely used screening test for macroprolactin and is easily performed in clinical laboratories.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…It has been generally accepted that a PEG-precipitation ratio greater than 60% (recovery less than 40%) is the cut-off value for the diagnosis of macroprolactinemia. This is because there is no a clear-cut value of "substantial increase", but conventionally a diagnosis of macroprolactinemia is made when more than 30-60% of PRL is in 11 the macroprolactin form of GFC [6,9,24,[26][27][28]. Precipitation with PEG is a widely used screening test for macroprolactin and is easily performed in clinical laboratories.…”
Section: Diagnosismentioning
confidence: 99%
“…Therefore macroprolactinemia develops due to the delayed clearance of PRL rather than increased production. These PRL autoantibodies are stable with time and long-term follow-up (>10 years) revealed that macroprolactinemia might be a longlasting condition in humans [3,4,19,28]. The second reason for the asymptomatic presentation of macroprolactinemia includes binding of anti-PRL autoantibodies to their binding sites (epitopes) in both N-and C-terminal residues of the PRL molecule which are located near the binding site 1 to PRL receptors.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The human prolactin gene (PRL) gene, located on chromosome 6p22.3 [2], encodes for a 220 aminoacids, 23 kDa monomeric protein originating from cleavage of the 26 kDa preprolactin molecule, which is mainly produced by the cells of the anterior pituitary and placenta, precisely by those of the decidualized endometrium [3]. The hormone has essential functions in regulating breast development and milk production in women, but also plays pleiotropic functions as osmoregulation, angiogenesis and immunoregulation [4]. The usual reference range in serum is comprised between 2-18 ng/mL in men and 2-30 ng/mL in women, respectively.…”
mentioning
confidence: 99%
“…> 30%-60%) of circulating prolactin isoforms with molecular weight > 100 kDa [6]. The overall prevalence of macroprolactinemia in the general population ranges between 3% and 4%, but remarkably increases, up to 35%, in patients with hyperprolactinemia [4]. A number of physiological and pathological conditions have been associated with macroprolactinemia, including stress, pregnancy, strenuous physical exercise, pituitary adenomas and cancers, mechanical stimulation of breast, chest wall trauma, hepatorenal disease, primary hypothyroidism, intracranial tumors compressing pituitary stalk or hypothalamus, empty sella syndrome, treatment with prolactin stimulating drugs (i.e.…”
mentioning
confidence: 99%
“…Usualmente, a isoforma mais prevalente é a monomérica, seguida da dimérica, sendo a macroprolactina responsável por menos de 5% da PRL total. No entanto, em 10% a 25% dos indivíduos hiperprolactinêmicos, a principal isoforma circulante é a macroprolactina, o que é denominado de macroprolactinemia (35). A macroprolactina na maioria dos casos é constituída pelo complexo PRL monomérica-imunoglobulina IgG e, por apresentar baixa atividade biológica (36), é uma situação benigna.…”
Section: Diagnósticounclassified